Oral Vitamin B12 Replacement for the Treatment of Pernicious Anemia - Chan, Catherine Qiu Hua (Front Med (Lausanne), 2016)
Many patients with pernicious anemia are treated with lifelong intramuscular (IM) vitamin B12 replacement. As early as the 1950s, there were studies suggesting that oral vitamin B12 replacement may provide adequate absorption. Nevertheless, oral vitamin B12 replacement in patients with pernicious anemia remains uncommon in clinical practice. The objective of this review is to provide an update on the effectiveness of oral vitamin B12 for the treatment of pernicious anemia, the recommended dosage, and the required frequency of laboratory test and clinical monitoring. Relevant articles were identified by PubMed search from January 1, 1980 to March 31, 2016 and through hand search of relevant reference articles. Two randomized controlled trials, three prospective papers, one systematic review, and three clinical reviews fulfilled our inclusion criteria. We found that oral vitamin B12 replacement at 1000 μg daily was adequate to replace vitamin B12 levels in patients with pernicious anemia. We conclude that oral vitamin B12 is an effective alternative to vitamin B12 IM injections. Patients should be offered this alternative after an informed discussion on the advantages and disadvantages of both treatment options.